Association between Anemia Severity and Left Ventricular Hypertrophy in Patients with Chronic Kidney Disease - Samiullah Khan, Sadullah Shah, Naimat Ullah Shah, Saeed Maqsood, Radhia Khan, Muhammad Saad Jibran (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anemia is one of the frequent complications that accompany chronic kidney disease (CKD) and leads to cardiovascular morbidity. Left ventricular hypertrophy (LVH), is a common disease among patients with CKD and it has poor prognosis. The severity of anemia and LVH, however, is not entirely characterized, especially in the local populations. Objective: To establish the correlation between the severity of anemia and the existence of the left ventricular hypertrophy among the patients with chronic kidney disease visiting the medical outpatient clinics. Methods: The study was a cross-sectional study, conducted at the Medical Teaching Institution Bannu and Medical Teaching institution DI Khan during six months between Feb 2022 and July 2022. The patients with adult CKD were recruited in a sequential manner and the demographic, clinical and laboratory information such as hemoglobin level were noted. Anemia was categorized as mild, moderate and severe. Each one of them was subjected to transthoracic echocardiography to determine the left ventricular mass and LVH. The severity of anemia and LVH were determined with chi-square and ANOVA tests and p<0.05 was taken as significant. Results: Among the 120 patients studied, 70 (58.3) patients had LVH. The frequency of LVH had an emetic relation with the severity of anemia: mild anemia (29.4%), moderate anemia (60.9%), and severe anemia (80.0%) (p<0.001). The mean left ventricular mass index was significantly more in patients with severe anemia than mild or moderate anemia. Further factors that were related to LVH were CKD stage and hypertension. Conclusion: The existence and extent of LVH in patients with CKD are closely related to intensified anemia. Timely detection and control of anemia could be beneficial particularly in minimizing cardiac remodelling and cardiovascular outcomes. Keywords: Anemia; Chronic kidney disease; Left ventricular hypertrophy; Cardiovascular risk.